Visionary Leadership Management in Strengthening Madrasah Quality Culture through School-Based Management Strategy (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Strengthening the quality culture of madrasas is a strategic need in facing the increasingly complex and sustainable demands for improving the quality of education. In this context, the visionary leadership of the madrasah principal plays a crucial role in directing organizational change through planned, participatory, and quality-oriented management. This study aims to analyze and describe visionary leadership management in strengthening the quality culture of madrasas through the School-Based Management strategy at Madrasah Aliyah Negeri 2 Karawang, East Karawang District. This study uses a qualitative approach with a case study type. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies, involving the madrasah principal, vice-principal, teachers, and education staff as research informants. The results of the study indicate that the visionary leadership of madrasah principals contributes significantly to strengthening the culture of quality through internalization of the vision, participatory leadership, leadership role models, continuous program evaluation, management transparency, teacher empowerment, and collaboration with stakeholders. The School-Based Management Strategy serves as an operational instrument that bridges the leadership vision with madrasah management practices. The implications of this study emphasize the importance of consistent and contextual visionary leadership as a basis for developing policies and practices to improve madrasah quality.